Some Combinatorial Identities of \(q\)-Harmonic and \(q\)-Hyperharmonic Numbers - Kızılateş, Can; Tuğlu, Naim (Communications in Mathematics and Applications, 2015)
In this paper, by means of \(q\)-difference operator we derive \(q\)-analogue for several well known results for harmonic numbers. Also we give some identities concerning \(q\)-hyperharmonic numbers.